The Influence of Ethical Environment on Employee Performance with Optimism as a Mediator - Dicky Ferlian Utama; Zainnur M. Rusdi (Economics and Digital Business Review, 2025)
This research investigates the impact of the ethical environment on employee performance, with optimism serving as a mediating variable. This research employs a cross-sectional survey design to gather primary data from 187 participants employed in A-accredited junior high schools in Bandar Lampung City. Validity and reliability assessments were performed to evaluate the extent of validity and reliability of the research instruments employed. A Kolmogorov-Smirnov test was performed to assess the normality of the collected data distribution. Descriptive statistical analysis and the Hayes process macro were employed to test the hypothesis. The test results confirm hypothesis 1, indicating that the ethical environment positively and significantly influences employee performance. The study's results confirm hypothesis 2, indicating that the ethical environment positively and significantly influences optimism. Hypothesis 3 posits that optimism exerts a positive and significant influence on employee performance. This study further supports hypothesis 4, which posits that optimism mediates the relationship between ethical environment and employee performance. It is essential for organisations to foster an ethical environment and cultivate optimism to enhance employee performance.